Increased liver stiffness in idiopathic pulmonary fibrosis: a pilot study - Bocchino, Marialuisa; Brancaccio, Giuseppina; Rea, Gaetano; De Martino, Marina; Gaeta, Giovanni Battista; Sanduzzi, Alessandro (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Purpose: There is evidence that pulmonary, hepatic and renal fibrosis may share common pathogenetic pathways. Aim of our study was to measure liver stiffness in patients affected by clinically stable idiopathic pulmonary fibrosis (IPF). Methods: Twenty-nine cases (24 M; mean age±SD: 67±8.3 yrs; 19 ex-smokers) along with fifteen age- and sex-matched healthy volunteers were enrolled. Liver conventional ultrasound examination and transient ultrasound elastography (TUE) were realized by two independent operators. Results: Mild/moderate steatosis was identified in 1 control and 8 IPF cases (6.6% and 27.5%); severe steatosis in 2 IPF patients (7%). Mean TUE measurements were increased in 11 IPF cases (38%) as compared to controls (6.4±2.2 kPa vs 5.2±0.4 kPa; p=0.02). Conclusions: To our knowledge, this is the first report suggesting that liver stiffness is increased in more than one-third of IPF patients. Application of novel methodologies should be encouraged for investigating further IPF.